Catch and release : the enduring yet vulnerable horseshoe crab - Moore, Lisa Jean, 1967- (NYU Press, 2018)
Based on a multimethod study that centers on interviews with over 30 conservationists, field biologists, ecologists, paleontologists and over 3 years of my fieldwork on urban beaches in the New York City area, the Florida Keys, and international conferences, 'Catch and Release' explores the interspecies relationships between humans and horseshoe crabs - our multiple sites of entanglement and enmeshment as we both come to matter.